Creation of institutions responsible for religious rehabilitation of the Republic of Kazakhstan and their functional duties (Eurasian Journal of Religious Studies, 2023)
The article deals with the complexity of the religious situation during the years of independence of the Republic of Kazakhstan, the adoption of legal acts to regulate religious issues, the creation of bodies responsible for religious issues, and their responsibilities. After gaining independence, Kazakhstan demonstrated religious freedom. However, he was not ready to deal with the problems associated with this religious freedom. The problems he caused began to disturb the peace of society. Even some religious radical movements threatened the constitutional structure of the state. New committees, departments and centers have been created in the structure of state administration to address these issues on the agenda. New states were opened from some law enforcement agencies. For the effective regulation of religious issues, it was necessary to coordinate the work of institutions in the state mechanism. And in order to prevent emerging religious threats, it became necessary to appropriately clarify the functional responsibilities of the relevant institutions. In particular, conducting an examination of religious literature and objects, making excuses for representatives of destructive religious movements, conducting explanatory work with them, de-radicalization, readaptation in society, increasing religious literacy of the general public, the formation of a stepped system of religious education.
Keywords: religion; law; prevention; rehabilitation; de-radicalization; probation